The effect of rice husk nanosilica hydroxyl compound on dentin biomineralization - Iffi Aprillia; Endang Suprastiwi; Aryo Megantoro; Luh Putu Trisna; Budi Utami; Sarmayana Yana (Wolters Kluwer Medknow Publications, 2021)
Rice husk nanosilica contains hydroxyl for dentin remineralization. The aim of this study was to analyze and correlate the ability of rice husk nanosilica to induce hydroxyapatite dentin. The detachment of hydroxyl from rice husk nanosilica was analyzed using the sol-gel and pyrolysis methods with Fourier transform infrared spectroscopy. Subsequently, exposing of the demineralized dentin to rice husk nanosilica was performed for a comparison. The formation of hydroxyapatite on dentin was analyzed using X-ray diffraction. The amount of hydroxyl released from the two methods was then correlated with the hydroxyapatite that formed at the dentin. The extraction of hydroxyl on rice husk nanosilica with two methods was the same. Analysis of the amount of hydroxyapatite dentin with both the methods corresponds to each other. The correlation test obtains the value of R = 0.656. Rice husk nanosilica has a similar capability to release hydroxyl compound and form hydroxyapatite dentin using two methods. The creation of hydroxyapatite dentin is not only caused by the exposure of rice husk nanosilica but also owing to other factors that might reinforce the process of hydroxyapatite formation.